2016
DOI: 10.1111/hel.12339
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer – clinical and epidemiological aspects

Abstract: Gastric cancer (GC) ranks fifth for cancer incidence and second for cancer deaths. Epidemiological data showed that survivors of Hodgkin's lymphoma and patients with pernicious anemia etiologically linked to autoimmune gastritis are at increased risk of GC. Screening of patients with autoimmune thyroid disease by means of pepsinogen (PG) I and PG I/II detected autoimmune gastritis with oxyntic gastric atrophy in one of four patients and may be recommended for GC prevention purposes. The International Agency fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 29 publications
(47 reference statements)
0
83
1
5
Order By: Relevance
“…In large-scale studies, the factors such as stage, metastasis are found to be related to disease progression [25]. While in the current study the relationship was not found, possibly due to the limited sample size.…”
Section: Discussioncontrasting
confidence: 60%
“…In large-scale studies, the factors such as stage, metastasis are found to be related to disease progression [25]. While in the current study the relationship was not found, possibly due to the limited sample size.…”
Section: Discussioncontrasting
confidence: 60%
“…Gastric cancer (GC) is a very common malignant tumor throughout the world, and it leads to cancer-related mortality rates that are higher than those of many other tumors 1. Although efforts toward early diagnoses and treatment for GC have made great progress, and we can frequently perform radical surgery for GC, the prognoses for patients with advanced GC are still very poor, and their 5-year survival rate remains in an unsatisfactory range of 10%–15% 2.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of H. pylori infection is a matter of debate because of several implications arising from the prevalence of the disease, the presence of symptoms, the potential evolution toward atrophic gastritis, metaplasia, gastric cancer and mucosa-associated MALT lymphoma. Current guidelines suggest eradication of H. pylori in all diagnosed subjects [1], as this infectious agent is included in the list of IARC group I carcinogens [2][3][4].…”
Section: Introductionmentioning
confidence: 99%